Usaha Perbanyakan Subang Gladiol (Gladiolus hibridus L) dengan Menggunakan Benziladenin (BA) - Tri Dewi Andalasari (Politeknik Negeri Lampung., 2011)
Gladiolus propagation effort has been experiencing problems because of active buds on gladiolus corms in normal conditions is generally. Shoots will grow and then will produce tubers. So for rapid multiplication of gladiolus necessary effort to stimulate active shoots found on gladiolus corms. The use of benzyl adenine was effective enough to stimulate the emergence of shoots on gladiolus corms. Earring size seedlings generally will affect the size of the new corms. In general, if the new corms are formed more than one will affect the size of the next Earring. Fertilization-rise is expected to enlarge the size of the corm so that it can directly be used as a corm production. This study aims to find methods of rapid propagation of gladiolus corms by: (1) the effect of initial corm size on the number and size of the new corm, (2) the effect of fertilization dose on the growth of earrings, and (3) the effect of fertilization at each dose respective initial corm size. This study is a continuation of previous studies that aimed to obtain an effective concentration of BA to stimulate the growth of shoots contained in gladiolus corms. This research used the BA 30 ppm (the results of previous studies) is applied to the gladiolus cultivars Kaifa. The treatment applied to the three sizes of 3.8 to 4.8 cm diameter Earring (U1), 2.5 to 3.7 cm (U2), 1.2 to 3.0 cm (U3). The results showed that administration with a concentration of 30 ppm BA, able to grow all of gladiolus corms which were attempted (100% sprout more than one bud), and capable of increasing the number of active buds and number of shoots by 4.6 by 6.4. Keywords: Gladiolus hibridus L, Benziladenin